Molecular, Endocrine, and Genetic Mechanisms of Arterial Calcification - Terence M. Doherty; Lorraine A. Fitzpatrick; Daisuke Inoue; Jian-Hua Qiao; Michael C. Fishbein; Robert Detrano; Prediman K. Shah; Tripathi B. Rajavashisth (2004)
Pathologists have recognized arterial calcification for over a century. Recent years have witnessed a strong resurgence of interest in atherosclerotic plaque calcification because it: 1) can be easily detected noninvasively; 2) closely correlates with the amount of atherosclerotic plaque; 3) serves as a surrogate measure for atherosclerosis, allowing preclinical detection of the disease; and 4) is associated with heightened risk of adverse cardiovascular events. There are two major types of calcification in arteries: calcification of the media tunica layer (sometimes called Mönckeberg’s sclerosis), and calcification within subdomains of atherosclerotic plaque within the intimal layer of the artery. There are important similarities and differences between these two entities. Of particular interest are increasing parallels between cellular and molecular features of arterial calcification and bone biology, and this has led to accelerating interest in understanding how and why bone-like mineral deposits may form in arteries. Here, we review the two major pathological types of arterial calcification, the proposed models of calcification, and endocrine and genetic determinants that affect arterial calcification. In addition, we highlight areas requiring further investigation.